Die Kunst als Mittelpunkt der Welt ausgewählte Briefe und Schriften - Friedrich, Caspar David 1774-1840 (textura, 2023)
BRIEFE -- AN JOHAN LUDVIG LUND, SEPTEMBER (?) 1800 -- AN JOHAN LUDVIG LUND, OKTOBER 1800 (?) -- AN JOHAN LUDVIG LUND, ENDE NOVEMBER 1800 -- AN JOHANN WOLFGANG VON GOETHE, DRESDEN, 25. AUGUST 1805 -- AN JOHANN WOLFGANG VON GOETHE, DRESDEN, 14. DEZEMBER 1805 -- AN PHILIPP OTTO RUNGE, DRESDEN, 4. OKTOBER 1808 -- AN CHRISTIAN FRIEDRICH, DRESDEN, 24./25. NOVEMBER 1808 -- AN JOHANNES SCHULZE, DRESDEN, 8. FEBRUAR 1809 -- AN JOHANNES SCHULZE, CA. AUGUST 1809 -- AN FRIEDRICH AUGUST KOETHE, DRESDEN, 18./19. AUGUST 1810 -- AN FRIEDRICH AUGUST KOETHE, DRESDEN, JANUAR 1811 -- AN FREDERIK CHRISTIAN SIBBERN, KRIPPEN, 30. MAI 1813 -- AN ERNST MORITZ ARNDT, DRESDEN, 12. MÄRZ 1814 -- AN LOUISE SEIDLER, DRESDEN, 2. MAI 1814 -- AN HEINRICH FRIEDRICH, DRESDEN, VERMUTLICH OKTOBER 1814 -- AN GOTTLOB FREIHERR VON BERLEPSCH, DRESDEN, 1. MAI 1815 -- AN LOUISE SEIDLER, DRESDEN, 9. MAI 1815 -- AN LOUISE SEIDLER, DRESDEN, 18. OKTOBER 1815 -- AN CHRISTIAN FRIEDRICH, DRESDEN, 28/29. MAI 1816 -- AN FRIEDRICH AUGUST I., KÖNIG VON SACHSEN, DRESDEN, 10. JUNI 1816 -- AN JOHAN LUDVIG LUND, DRESDEN, 11. JULI 1816 -- AN DIE VERWANDTEN IN GREIFSWALD, 28. JANUAR 1818 -- AN DEN RAT DER STADT STRALSUND, DRESDEN, VERMUTLICH UM DEN 31. JANUAR 1818 -- AN HEINRICH FRIEDRICH, DRESDEN, 26. MÄRZ 1818 -- AN CHRISTIAN FRIEDRICH UND ADOLF FRIEDRICH, DRESDEN, 12./15./28./30. AUGUST 1819 -- AN HEINRICH FRIEDRICH, DRESDEN, 13. MAI 1820 -- AN CHRISTIAN FRIEDRICH, DRESDEN, 22. AUGUST 1820 -- AN ADOLF FRIEDRICH, DRESDEN, 29. DEZEMBER 1820 -- AN CAROLINE FRIEDRICH, DRESDEN, 10./11. JULI 1822 -- AN CAROLINE FRIEDRICH, DRESDEN, 12./13. JULI 1822 -- AN ADOLF FRIEDRICH, DRESDEN, 1./20. JANUAR 1824 -- AN WASSILI A. SHUKOWSKI, DRESDEN, 9. FEBRUAR 1830 -- AN DIE BRÜDER, DRESDEN, 11. SEPTEMBER 1830.